THE RELATIONSHIP BETWEEN NURSE’S KNOWLEDGE ABOUT NURSING CARE AND PATIENT’S SATISFACTION - Sylvie Puspita; Enny Puspita (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Caring of nurses is an important component in evaluating patient satisfaction. Nurses have a big influence in determining the quality of hospital services (Rumagit, Mulyadi, & Malara, 2017).Objectives: The purpose of this study was to analyze the relationship between nurse's knowledge of nursing care and patient's satisfaction.Methods: The design of this study used descriptive correlation design with cross sectional approach. The population in this study were all nurses and patients in Asoka and Flamboyan rooms of the General Hospital of Jombang Regency. The sampling technique used Purposive Sampling with following criteria: cooperative patient, patient awareness composer, able to read and write. The sample in this study were all of Nurse Associated or who did the nursing care to patients totaling 26 people consisting of 15 nurses of Flamboyan room and 11 nurses of Asoka room. For assessing the satisfaction of the sample patients, the sample of this study were 11 patients of Asoka room and 15 patients of Flamboyan room who will return home after being hospitalized. Instrument of this study used modification of Nurse’s Knowledge about Nursing Care Questionnaire developed by Surjiyem (2017) consist of 20 items with Cronbach Alpha .635 and Patient Satisfaction Questionnaire developed by General Hospital of Jombang Regency consist of 20 items with Cronbach Alpha .660. The data of this study were analyzed by Fisher’s Exact Test with significance value less than .05.Results: Based on the research results obtained Exact Sig. (2-sided) .010, which means there is a relationship between nurses' knowledge and patient satisfaction.Conclusion: Nurse’s knowledge about nursing care related to patient’s satisfaction. Based on the results of this study, the nurses are expected to have good knowledge in nursing care, so they can provide optimal services and provide satisfaction to patients and families for these services. Keywords: Nurse’s Knowledge, Nursing Care, Patients Satisfaction